Application of multimodal standardized analgesia under the concept of enhanced recovery after surgery in laparoscopic radical colorectal cancer surgery - Cao, Lu; Zhang, Le; Chen, Baoyu; Yan, Likun; Shi, Xianpeng; Tian, Lifei (Frontiers in Oncology, 2024)
Aims: To observe the efficacy and safety of multimodal standardized analgesia in patients undergoing laparoscopic radical colorectal cancer surgery. Methods: A prospective, double-blind, randomized study of patients who were admitted to our hospital between December 2020 and March 2022 with a diagnosis of colorectal cancer and who intended to undergo elective laparoscopic radical colorectal cancer surgery was conducted. The participants were randomly divided into two intervention groups, namely, a multimodal standardized analgesia group and a routine analgesia group. In both groups, the visual analogue scale (VAS) pain scores while resting at 6 h, 24 h, 48 h and 72 h and during movement at 24 h, 48 h and 72 h; the number of patient controlled intravenous analgesia (PCIA) pump button presses and postoperative recovery indicators within 3 days after surgery; the interleukin-6 (IL-6) and C-reactive protein (CRP) levels on the 1st and 4th days after surgery; and the incidence of postoperative adverse reactions and complications were recorded. Results: Compared with the control group, the multimodal standardized analgesia group had significantly lower VAS pain scores at different time points while resting and during movement (P<0.05), significantly fewer PCIA pump button presses during the first 3 postoperative days (P<0.05), and significantly lower IL-6 and CRP levels on the 1st postoperative day (P<0.05).There was no statistically significant difference in the time to out-of-bed activity, the time to first flatus, the IL-6 and CRP levels on the 4th postoperative day or the incidence of postoperative adverse reactions and complications between the two groups (P >0.05). Conclusion: For patients undergoing laparoscopic radical colorectal cancer surgery, multimodal standardized analgesia with ropivacaine combined with parecoxib sodium and a PCIA pump had a better analgesic effect, as it effectively inhibited early postoperative inflammatory reactions and promoted postoperative recovery and did not increase the incidence of adverse reactions and complications. Therefore, it is worthy of widespread clinical practice.